Produção e caracterização de biocarvão de bagaço de laranja para utilização no pós-tratamento de água residuária - Carvalho, Roseanne Santos de (2018)
Due to the growing problem of water scarcity, as well as the need to preserve the environment, studies have been conducted aiming at the reuse of agroindustrial waste so that biofuels can be produced to promote the reuse of wastewater in crop irrigation as well as used in the removal of emerging micropollutants in wastewater. The bioadsorption arouses great interest in the research of new materials that can be used as adsorbents, because it presents a promising, efficient, economically viable and ecologically sustainable proposal when compared to other decontamination methods. In this context, the present study was based on the production of a biochar from the orange bagasse at 550oC to compose a tertiary treatment in the tetracycline retention as well as the use of the effluent in the irrigation of the radish culture. Samples of in natura orange pomace, biochar and activated commercial charcoal were characterized. The samples were characterized by thermogravimetry, surface area and porosity measurements, scanning electron microscopy and X-ray diffraction. Irrigation with the filtered effluent with activated charcoal and biocarbon did not influence representatively the agronomic variables of the culture, the physical- chemical properties of water and effluents were met by the aforementioned resolution and / or work on the subject. He observed the risk of salinization and sodification of the soil by the practice. The Langmuir model was the one that best adapted to the biochar, configuring adsorption of physical nature, beneficial to the desorption process. The kinetic model that fitted the most was the pseudo-second order and the estimated equilibrium time for the biochar was eight minutes. The spectrophotometric method was safe, economical and feasible in all the analyzes used. The biocarbon had a capacity of 100% tetracycline adsorption in domestic wastewater and the efficiency of the filtration with biochar was on average 25% higher than with the commercial coal. In view of the above, the possibility of converting a waste from the low-value agro-industry and without appropriate destination to a value-added product, orange marc bagasse, to be used as a tertiary treatment for reuse of effluent in irrigation and as adsorbent for the removal of tetracycline in domestic wastewater.